Refugee Mental Health, Global Health Policy, and the Syrian Crisis - Cratsley, Kelso; Brooks, Mohamad Adam; Mackey, Tim K. (Frontiers in Public Health, 2021)
The most recent global refugee figures are staggering, with over 79.5 million forcibly displaced people, 26 million registered refugees, and 107,800 resettled in third countries. The ongoing conflict in Syria is a major contributor. After a decade of violence and destabilization, approximately 13.2 million Syrians have been displaced from their homes, including 6.7 internally displaced persons, and over 6.6 million refugees registered in other countries. Beyond the immediate political and economic challenges, an essential component of any response to this humanitarian crisis must be health-related, including policies and interventions specific to mental health. This policy and practice review addresses refugee mental health in the context of the Syrian crisis, providing a broad overview of the current situation while exploring new initiatives in mental health research and global health policy that can help support the strengthening and expansion of services. Relevant global mental health policy frameworks are first briefly introduced, followed by a discussion of recent research on refugee mental health. We then provide an update on the current status of research, service provision, and health policy in several of the leading destinations for Syrians who have been forcibly displaced. This starts within Syria itself, then turns to Turkey, Lebanon, Jordan, and Germany. Several research and policy recommendations are discussed, including the pressing need for more data at each phase of migration, the strengthening of integrated and cross-border mental health services, and the explicit inclusion of refugee mental health in both national and global health policy.